Urinary tract infections and antimicrobial susceptibility: A retrospective trend analysis of uropathogens in women in Accra, Ghana (2019–2022) - Innocent Afeke; Joseph Adu-Amankwaah; Abdul-Wahab Mawuko Hamid; Precious Kwablah Kwadzokpui; Enoch Aninagyei; Glona Emmanuel; John Gameli Deku (PLoS ONE, 2025)
Urinary tract infections (UTIs) remain a significant public health concern, with evolving patterns in prevalence and antimicrobial resistance. This retrospective study, conducted at the Greater Accra Regional Hospital in Accra, Ghana, analyzed 11,280 urine cultures obtained exclusively from female patients from 2019 to 2022 to assess trends in UTI burden, prevalence stratified by age and month, and antimicrobial susceptibility patterns. In all, urine pathogens were isolated in 4475 (39.67%) of the samples tested. Of the total number of uropathogens isolated, majority of them were bacterial pathogens (94.21%), with an increasing proportion of fungal infections, specifically candida species (5.79%). Irrespective of the year, the highest prevalence of uropathogens were consistently recorded in the month of May, while individuals aged ≥  90 years exhibited the greatest odds of infection in 2020 (aOR: 1.88, p = 0.039). Escherichia coli (30.51%) and Staphylococcus aureus (15.16%) were the most prevalent Gram-negative and Gram-positive pathogens, respectively. Antimicrobial susceptibility testing revealed declining antibiotic effectiveness over time, with notable exceptions for gentamicin (97.4% effectiveness against Enterococcus spp.) and ofloxacin (82.9% against Enterococcus spp.). Alarmingly, most antibiotics exhibited effectiveness rates below 20% by 2022, underscoring the growing resistance challenge. These findings, drawn from a key healthcare facility in Ghana’s capital, highlight the dynamic nature of UTIs and the urgent need for targeted interventions, optimized antimicrobial stewardship, and continuous monitoring of resistance patterns to improve patient outcomes.